The Role of Informatics in Developing Vocational Performance of Vocational Teachers in Industrial Schools in Palestine: from the Principles and Vices Point of View - Watheq Najeeb Mahmoud Hathnawi (My University, 2009)
This study aimed to define the the role of informatics in developing vocational performance of vocational teachers in industrial schools in Palestine from the views of the principals and teachers, and tried to determine the effects of certain variables on evaluating the role of informatics in developing vocational performance of vocational teachers in industrial schools in Palestine. Concerning the variables related to the principals and teachers; they are (gender, job, academic qualification, family of scientific specialization, years of experience, sponsor, governorate, internet availability, computer availability, LCD availability, local computer network availability, educational software availability), also it aimed at determining the problems of informatics utilizing in industrial schools in Palestine. For the purpose of this study, available sample was used for the principals and teachers. The sample consisted of (188) principal and teacher forming (83%) of the study population. Questionnaire was developed to fulfill the aims of the study; it consisted of (4) parts, part 1 included primary information, part 2 included general information a bout what exist in school, part 3 included (44) items of questionnaire, these items were distributed over (3) areas(knowledge-ware, soft-ware, hard-ware). Part 4 included a question about problems of informatics utilizing in industrial schools in Palestine. For establishing the instrument reliability, the reliability coefficient was computed using cronbach Alfa formula for questionnaire. The obtained reliability coefficient was (0.89). This value was so reliable to fulfill the aims of the study. To analyze the data statistically, means percentages, t-test, One way Anova analysis of variance and (LSD) test were used. The findings of the study indicated the following: - Concerning the total degree of the role of informatics in developing vocational performance of vocational teachers in industrial schools in Palestine from the views of the principals and teachers was very great, it was (83.2%). - Lack of technical and specialized training for vocational teachers came first among the existing problems of informatics utilizing in industrial schools in Palestine., while the difference of equipments in industrial schools came last. The percentages of these problems were (15.9%) and (1.3%) in order. - There were no significant differences (α= 0.05) related to the evaluation of the role of informatics in developing vocational performance of vocational teachers in industrial schools in Palestine from the views of the principals and teachers due to(gender, jop, sponsor, governorate, internet availability, LCD availability, local-computer-network availability, educational software availability). - There were significant differences (α= 0.05) related to evaluation the role of informatics in developing vocational performance of vocational teachers in industrial schools in Palestine from the views of the principals and teachers due to (academic qualification, family of scientific specialization, years of experience, computer availability).The differences were between Diploma and Master in favour of Master, and between the family of Electricity and otherwise family in favour of the family of Electricity, and between less than (5) years experience and more than (10) years experience in favour of less than (5) years experience, and between computer availability and not computer availability in favour of computer availability. On the basis of these findings, the researcher recommended the following: 1.Saving of informatics component in industrial secondary schools in Palestine (knowledge-ware, soft-ware, hard-ware). 2.Utilizing Information and Communication Technology (ICT) in all activities of the industrial secondary schools in Palestine. 3.Great interest of human resources development in industrial secondary schools in Palestine in order to update new technologies and cope information pollution.

هدفت هذه الدراسة التعرف إلى دور المعلوماتية في تنمية الأداء المهني للمعلمين المهنيين في المدارس الثانوية الصناعية في فلسطين من وجهة نظر المديرين والمعلمين المهنيين، إضافة إلى تحديد أثر متغيرات (الجنس، والوظيفة، والمؤهل العلمي، وعائلة التخصص العلمي، وسنوات الخبرة، والجهةالمشرفة، والمحافظة، وتوفر خدمة الإنترنت، وتوفر جهاز حاسوب، وتوفر جهازعرضLCD، وتوفر شبكة حاسوب محلية، وتوفر برمجيات تعليمية أو تدريبية) من وجهة نظر المديرين والمعلمين على تقييم دور المعلوماتية في تنمية الأداء المهني للمعلمين المهنيين في المدارس الثانوية الصناعية في فلسطين. كما هدفت إلى تعرف أهم المشكلات التي تحد من توظيف المعلوماتية في المدارس الثانوية الصناعية في فلسطين. ولتحقيق ذلك أجريت الدراسة على عينة متيسرة من المديرين والمعلمين المهنيين قوامها (188) مديراً ومعلماً مهنيا تشكل (83%) من مجتمع الدراسة، وقد تم جمع البيانات باستخدام إستبانة تكونت من أربعة أقسام: القسم الأول يتضمن معلومات أولية، والقسم الثاني يتضمن معلومات عامة عن موجودات المدرسة، والقسم الثالث يشمل فقرات الإستبانة وعددها(44) فقرة موزعة على ثلاثة مجالات هي: مجال الموارد المعرفية، ومجال البرمجيات، ومجال الأجهزة والعتاد، أما القسم الرابع فيتضمن سؤالاً حول أهم المشكلات التي تحد من توظيف المعلوماتية في المدارس الثانوية الصناعية في فلسطين. وقد بلغ معامل الثبات الكلي للأداة باستخدام معادلة كرونباخ ألفا إلى (0.89) وهو معامل عال يفي بأغراض الدراسة. وقد تم معالجة البيانات إحصائياً باستخدام المتوسطات الحسابية والنسب المئوية، واختبار (ت) لمجموعتين مستقلتين، وتحليل التباين الأحادي، واختبار(LSD) للمقارنات البعدية بين المتوسطات الحسابية. وتوصلت الدراسة إلى النتائج التالية: - أن الدرجة الكلية لدور المعلوماتية في تنمية الأداء المهني للمعلمين المهنيين في المدارس الثانوية الصناعية في فلسطين من وجهة نظر المديرين والمعلمين كانت كبيرة جداً حيث وصلت النسبة المئوية للإستجابة عليها (83.2%)، وكان مجال الأجهزة والعتاد في المرتبة الاولى بنسبة (83.5%) ومجال البرمجيات في المرتبة الثانية بنسبة (83.3%) ومجال الموارد المعرفية في المرتبة الثالثة بنسبة(82.7%). - أكثر المشكلات التي تحد من توظيف المعلوماتية في المدارس الثانوية الصناعية في فلسطين من وجهة نظر المديرين والمعلمين هي ندرة الدورات الفنية التخصصية للمعلمين المهنيين حيث وصلت النسبة الى (15.9%)، وكانت أقل المشكلات هي اختلاف التجهيزات بين المدارس الثانوية الصناعية المختلفة حيث وصلت النسبة الى (1.3%) - لا توجد فروق ذات دلالة إحصائية عند مستوى الدلالة (α = 0.05) في تقييم دور المعلوماتية في تنمية الأداء المهني للمعلمين المهنيين في المدارس الثانوية الصناعية في فلسطين من وجهة نظر المديرين والمعلمين المهنيين تعزى لمتغيرات (الجنس، والوظيفة، والجهة المشرفة، والمحافظة، وتوفر خدمة الإنترنت، وتوفر جهاز عرض LCD، وتوفر شبكة حاسوب محلية، وتوفر برمجيات تعليمية أو تدريبية). - توجد فروق ذات دلالة إحصائية عند مستوى الدلالة (α = 0.05) في تقييم دور المعلوماتية في تنمية الأداء المهني للمعلمين المهنيين في المدارس الثانوية الصناعية في فلسطين من وجهة نظر المديرين والمعلمين المهنيين تعزى لمتغيرات (المؤهل العلمي، وعائلة التخصص العلمي، وسنوات الخبرة، وتوفر جهاز حاسوب)، حيث كانت الفروق بين الدبلوم والماجستير ولصالح الماجستير، وبين عائلة الكهرباء وعائلة غير ذلك ولصالح عائلة الكهرباء، وبين من خبرتهم أقل من (5) سنوات وممن خبرتهم أكثر من (10) سنوات ولصالح من خبرتهم أقل من (5) سنوات، وبين من يتوفر لهم جهاز حاسوب وممن لا يتوفر لهم جهاز حاسوب، ولصالح من يتوفر لهم جهاز حاسوب. وفي ضوء أهداف الدراسة ونتائجها أوصى الباحث بعدة توصيات أهمها: - ضرورة توفير جميع عناصر المعلوماتية في المدارس الثانوية الصناعية من موارد معرفية وبرمجيات وأجهزة وعتاد. - ضرورة العمل على توظيف تكنولوجيا المعلومات والاتصالات في جميع الأنشطة الإدارية والتربوية والتعليمية والتدريبية في المدارس الثانوية الصناعية. - ضرورة الإهتمام بتنمية الموارد البشرية العاملة في المدارس الثانوية الصناعية لتتمكن من مواكبة التطورات التكنولوجية المتسارعة ومواجهة الإنفجار المعرفي. - العمل على تحقيق التكامل والتوازن بين التنمية المهنية للمعلمين المهنيين من جهة، وبين تطوير وتحديث الأجهزة والوسائل والأساليب التعليمية والتدريبية من جهة اخرى.
دور المعلوماتية في تنمية الاداء المهني للمعلمين المهنيين في المدارس الثانوية الصناعية في فلسطين - من وجهة نظر المديرين ونوابهم